Understanding English grammar : a course book for Chinese learners of English - Hung, Tony T. N. (Hong Kong University Press, 2005)
The book is designed for students' learning on their own as well as in a classroom. Each chapter is accompanied by a separate 'students' notes', which the students can consult after working through all the data and exercises in each chapter, to check their own answers and to read further explanations on the grammatical points in question.